Analysis of the flood risk incorporated into the regional and urban planning regulations of Argentina - Paula Andrea Zapperi (Investigaciones Geográficas)
The aim of this paper is to identify the degree to which typical elements of the fluvial and hydrological dynamics have been incorporated into regional and urban planning regulations in Argentina. Therefore, national and provincial regional and urban planning regulations were analyzed. The environmental laws that regulate aspects that influence the generation of water excess were also considered. When choosing the variables of analysis the references focused on the environmental studies as well as the establishment of the rules of use according to the flood risk. A coordination search between scales and sectors in risk management was identified according to the Law 27287/16 for the creation of the National System for Comprehensive Risk Management and Civil Protection. Meanwhile Spatial Planning approaches are minor. The lack of a national law to unify criteria regarding the authorization of new areas for urbanization has favored the diversity of directives that regulate urban expansion and floodplain occupation. The use of the river shoreline to delimit flood risk areas is also highlighted. However, this figure was proposed to set the boundaries over public domain in the riparian areas. Likewise, it is important to highlight the obligation imposed by Law 27287/16 on risk cartography as an instrument to convey the risks of the territory and as a basis to regulate its occupation.